GFAAS determination of mercury in muscle samples of fish from Amazon, Brazil - Moraes, Paula M. [UNESP]; Santos, Felipe A. [UNESP]; Cavecci, Bruna [UNESP]; Padilha, Cilene C.F. [UNESP]; Vieira, Jose C.S. [UNESP]; Roldan, Paulo S.; Padilha, Pedro de M. [UNESP] (Elsevier, 2013)
In the present study, a simple, rapid and sensitive method was developed for the determination of mercury concentrations in the muscle tissue of fish from the Brazilian Amazon using graphite furnace atomic absorption spectrometry (GFAAS) following acid mineralization of the samples in an ultrasonic cold water bath. Using copper nitrate as a chemical modifier in solution and sodium tungstate as permanent modifier, we were able to attain thermal stabilization of the mercury up to the atomisation temperature of 1600 °C in the GFAAS assay. The calculated limits of detection (LOD) and quantification (LOQ) were 0.014 and 0.047 mg kg-1, respectively. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Amazon fish; Chemical modifier; GFAAS; Mercury in fish; Permanent modifier